The rural as a space for the construction of knowledge and decisions in the life of young people - Massena, Fábio dos Santos; Sousa, Enzo Yuri Ferreira; Nascimento, Ian Felipe (Seven Editora, 2023)
The human being, throughout his development, builds his personality and, from adolescence, many changes occur in the person's life, added to the new thoughts and ways of acting that arise. These transformations lead young people to look at their living space and at the activity developed by the family in an analytical and critical way, making them reflect on the present reality. Given this scenario, the present work sought to know the vision of young people in 3 Family Farming communities in the Southern Region of Bahia in relation to their perception of the place where they live and the family farming activity. The objectives were operationalized through the application of forms, following the ethical precepts of Resolution 466/12. The results indicate that the local youth still perceive the place as pleasant and with the potential to provide a pleasant life, however, as a professional possibility, Family Farming is not an option for the majority. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-015